1967
DOI: 10.1021/ac60252a033
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric determination of trace levels of oxygen in gases with the photochemically generated methyl viologen radical-cation

Abstract: for 1M anion and 1M solvating agent concentrations. The varying magnitudes of these extraction constants may be attributed to the increasing acidity of the proton of the solvating species in the order chloroform < -amyl alcohol < pzerz-butylphenol.Effect of ZVjiV-Dimethylcaprylamide on Solvating Agent.It was of interest to determine if the schematic model postulated in Case I was reasonable. This was done by utilizing an electron donor solvating agent. This agent would not be expected to enhance partitioning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…No attempt was made to determine the absolute quantum yield. Sweetser (1967) reported that photoreduction of methyl viologen by EDTA at p H 6 at 450 nm with catalytic quantities of proflavin had a quantum yield of 0.6. For each catalyst the rate of reduction of methyl viologen with the same intensity of the same incident light source was determined.…”
Section: Methodsmentioning
confidence: 99%
“…No attempt was made to determine the absolute quantum yield. Sweetser (1967) reported that photoreduction of methyl viologen by EDTA at p H 6 at 450 nm with catalytic quantities of proflavin had a quantum yield of 0.6. For each catalyst the rate of reduction of methyl viologen with the same intensity of the same incident light source was determined.…”
Section: Methodsmentioning
confidence: 99%
“…The vacuum system included a liquid-nitrogencooled trap, and the inert gas (argon) was scrubbed to below 1 ppm 02 by passage over H2-activated BTS catalyst (Kontes Qlass Co.) at 200'C. Oxygen in the inert gas stream was measured by the method of Sweetser (16). The serum cap and stopcock on the sidearm of the Thunberg-EPR tube allows one to degas the system empty, with five or more cycles of gassing and evacuation, with the sidearm stopcock open.…”
Section: Methodsmentioning
confidence: 99%
“…O2 -according to the manufacturer) led to a 50% decrease in activity of the oxidase, thus indicating that the K , value for the pure oxidase must be very low (probably less than 1 p~). Complete removal of O2 by passing the N2 through the solution of Sweetser (1967) prior to sparging the reaction mixture completely prevented oxidation of cytochrome c by the added oxidase.…”
Section: The Oxidation Of Artijicial Electron Donors and Of Variousmentioning
confidence: 99%